1989
DOI: 10.1111/j.1600-0722.1989.tb01433.x
|View full text |Cite
|
Sign up to set email alerts
|

Hypersensitivity reactions to dental materials in a referred group of patients

Abstract: – 151 patients referred to the Department of Oral Diagnosis, University of Umeå, for investigation regarding potential side‐effects of dental materials were subjected to epicutaneous testing at a dermatology clinic. Twelve persons in this group had oral mucosal changes. Among the 151 patients 39 women and 7 men had positive skin reactions to one or more of the test substances used. The majority of the positive reactions were related to metals, particularly nickel, but a number of positive reactions to organic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
4

Year Published

1990
1990
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 22 publications
0
22
0
4
Order By: Relevance
“…In the humid environment of the oral cavity all alloys undergo corrosion, at least to a certain extent. 9 A number of factors can affect the process of ion release by an alloy: Manufacturing method; bracket surface characteristics; features of the environment in which brackets are inserted, such as composition, temperature, pH, bacterial flora, enzyme activity and the presence of proteins; 10 in addition to factors such as alloy usage (aging), which may be subject to adverse conditions such as stress, heat treatment, recycling or reuse of components, among others. 2) What can be done to reduce the biodegradation of metal brackets?…”
Section: Editor's Summarymentioning
confidence: 99%
“…In the humid environment of the oral cavity all alloys undergo corrosion, at least to a certain extent. 9 A number of factors can affect the process of ion release by an alloy: Manufacturing method; bracket surface characteristics; features of the environment in which brackets are inserted, such as composition, temperature, pH, bacterial flora, enzyme activity and the presence of proteins; 10 in addition to factors such as alloy usage (aging), which may be subject to adverse conditions such as stress, heat treatment, recycling or reuse of components, among others. 2) What can be done to reduce the biodegradation of metal brackets?…”
Section: Editor's Summarymentioning
confidence: 99%
“…Allergies to chromium salts are found in less than 1% of both genders. Allergies to palladium [8,9] and to gold, cobalt and copper [9] usually accompany nickel salt allergies. Previously, allergic reactions in the oral cavity to chromium alloys or in patients with metal restorations were thought to be exceptionally rare [10], but in recent years the number of patients with diagnosed dermal allergies to the most commonly used metal alloy components has grown rapidly [3,4,[11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…In the humid environment of an oral cavity, all alloys are susceptible to corrosion, if only to some extent. 6 Menezes et al 7 analyzed structural and chemical alterations in several metallic brackets, and observed that the wrinkled surface of new brackets makes them more susceptible to the corrosive process, and consequently the release of metallic ions.…”
Section: Introductionmentioning
confidence: 99%